2014
DOI: 10.1038/bjc.2014.150
|View full text |Cite
|
Sign up to set email alerts
|

Does cancer risk increase with HbA1c, independent of diabetes?

Abstract: Background:The risks for several cancer types are increased in people with diabetes. Hyperglycaemia, hyperinsulinaemia, inflammation and altered hormonal concentrations are common characteristics between the two diseases and can all be linked to hyperglycaemia.Methods:Here, we use glycated haemoglobin (HbA1c) as a biomarker for chronic hyperglycaemia. We explore whether cancer risk increases with HbA1c, independent of diabetes, and, therefore, if risk is already increased below the diabetic HbA1c range, by ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 52 publications
(91 reference statements)
4
70
0
2
Order By: Relevance
“…Also in our recently published study the risk of malignancy tended to increase with the duration of diabetes [7]. The impact of poor metabolic control on elevated cancer risk was documented in the meta-analysis by de Beer and Liebenberg [28], and was also observed in our previous study [7]. Epidemiological and clinical data indicate also higher cancer prevalence among elderly compared to younger patients [29,30].…”
Section: Discussionsupporting
confidence: 62%
“…Also in our recently published study the risk of malignancy tended to increase with the duration of diabetes [7]. The impact of poor metabolic control on elevated cancer risk was documented in the meta-analysis by de Beer and Liebenberg [28], and was also observed in our previous study [7]. Epidemiological and clinical data indicate also higher cancer prevalence among elderly compared to younger patients [29,30].…”
Section: Discussionsupporting
confidence: 62%
“…Given that up to 27% of diabetes is undiagnosed 3 , this could have skewed our groups. Similarly, we had no information regarding degree of diabetic control, which also may impact outcomes 39 . Additionally, information regarding the length of diagnosis and burden of diabetes was not captured in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the other role of glucose rather than an energy source. Recently, the direct effect of high glucose in increasing the risk of cancer was demonstrated [34]. It was shown that chronic hyperglycemia, indicated by elevated an glycohemoglobin or hemoglobin test (A1C), was associated with increased risk of several cancers independently of the DM status.…”
Section: A Possible Molecular Linkage Of Dm and Ccamentioning
confidence: 99%